Profitabilitas Memoderasi Pengaruh Corporate Social Responsibility dan Good Corporate Governance Pada Nilai Perusahaan - Dinata, I Dewa Agung Ade Krisna; Tenaya, Agus Indra (E-Jurnal Akuntansi; Vol 24 No 1 (2018), 2018)
Corporate Social Responsibilty is a form of business in maximizing the positive impact of the company's operations, it affects stakeholders both economically, socially, and environmentally. Good Corporate Governance is an effective protection to prevent any agency problem. Business and protection is done is a signal of information addressed to investors in decision-making related to the company. The purpose of this research is to obtain empirical evidence of Corporate Social Responsibilty and Good Corporate Governance influence on company value, and to know profitability as moderate variable influence Corporate Social Responsibilty and Good Corporate Governance on budget slack. This study was conducted on 8 companies that follow CGPI ranking within four years. Data analysis technique used in this research is Moderated Regression Analysis (MRA). The result of this research stated that Corporate Social Responsibilty and Good Corporate Governance have positive effect on company value, profitability can moderate (reinforce) influence Corporate Social Responsibility and Good Corporate Governance at company value.